Thumb Injuries and Instabilities. Part 2: Spectrum of Lesions - Blum, Alain G.; van Holsbeeck, Marnix T.; Bianchi, Stefano (Seminars in Musculoskeletal Radiology, 2021)
The motor function of the thumb and its alignment with regard to the hand make it particularly vulnerable to trauma. Pathology encountered in this joint is varied, and imaging techniques play a crucial role in the diagnosis and characterization of injury. Despite advances in imaging technology, acute thumb injuries remain a challenge for radiologists. Currently, standard radiography and ultrasonography are frequently used first-line imaging techniques. Computed tomography is most often indicated for complex fractures and dislocations. Magnetic resonance imaging may be used to optimally characterize soft tissues and bone marrow. In this article, we cover the most common traumatic injuries: fractures, dislocations, collateral ligament injuries of the metacarpophalangeal joint, as well as soft tissue lesions.
Keywords: Stener's lesion; thumb metacarpophalangeal joint injuries; ulnar collateral ligament; sesamoid fractures; foreign body